2ND EUROPEAN CONGRESS – FIEP (Fiep Bulletin - online, 2012)
The participants of 1st Serbian Congress Pedagogists of Physical Education and 2nd EuropeanCongress – FIEP, held in September, 2nd to 5th 2004, in Vrnjacka Banja, discussed the conditions andthe problems in the physical education as well as its incorporation into certain European institutaions.Based upon the presented expert expose and the corresponding discussion the following hasbeen proclaimed.